Estudo da qualidade do ar atmosférico de Uberlândia-MG no contexto da pandemia de Covid-19 - Duarte, Vinícius Melo (2021)
Uberlândia-MG is the largest city in the interior of the state and the fourth in the interior of Brazil, with a population of 706,597 in 2021, and a fleet of 0.693 vehicle/inhabitant, way above the national average, a factor that directly impacts the region's atmospheric air quality. The years 2020 and 2021 were atypical due to the pandemic caused by the severe acute respiratory syndrome 2 coronavirus (SARS-CoV-2). The forced reduction in the circulation of vehicles across the planet caused a momentary improvement in the quality of atmospheric air. The objective of the work was to study the air quality of Uberlândia during the period in which the city underwent temporary restrictions due to the pandemic, by measuring the concentration of three of the pollutants covered by Conama Resolution 491/2018: Total Suspended Particles (TSP), Inhalable Particles (PM10) and Ozone (O3). Statistical analyzes were performed using box plot graphs and correlation coefficients. During the period of more intense restrictions, the concentration of TSP was, on average, 21.2% below the respective months compared to the historical record from 2003 to 2018. As for PM10, the improvement in air quality was 58.1%. However, after the relaxation of restrictions, atmospheric air quality deteriorated again. From winter 2020 (period of strong restrictions) to winter 2021 (after the relaxation of restrictions), the average increase in the concentration of TSP in atmospheric air was 41.5%, while the increase for PM10 was 39.1%. During the study period, air quality was considered good in 100% of the measurements referring to the daily averages of TSP; in 96.4% of the daily averages of PM10 and in 98.2% of the hourly averages of ozone. Regarding the Covid-19 pandemic, data analysis showed that the number of new daily cases of the disease contributed to people staying at home, improving atmospheric air quality, which suggested that reducing pollution is an issue of people's awareness.